(untitled) (World Bulletin of Social Sciences, 2022)
The article examines the theoretical and practical aspects of the phenomenon of global governance and argues that globalization as a socio-political phenomenon is the modern phase of capitalism. The essence and trends of the emergence and development of global capitalism are revealed, the reasons for its emergence, description, degree of spread and differences from the old capitalism are analyzed.